Meningkatkan Hasil Belajar IPA Melalui Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Pada Murid Kelas V SD YPK Pniel Turu - Desy Putri Sahara; Andi Nurhartina; Susanti Fakaubun (Civiliza Publishing, Indonesia., 2026)
This study aims to improve the learning outcomes of Natural Sciences (IPA) through the implementation of the Two Stay Two Stray (TSTS) cooperative learning model for fifth-grade students of SD YPK Pniel Turu. The study used the Kurt Lewin Classroom Action Research (CAR) approach which was implemented in two cycles, each consisting of planning, action implementation, observation, and reflection. The research subjects were 16 fifth-grade students in the even semester of the 2025/2026 academic year. Data were collected through observations of teacher and student activities and learning outcome tests at the end of each cycle. Data were analyzed using quantitative and qualitative descriptive analysis. The results showed that the implementation of the Two Stay Two Stray cooperative learning model was able to improve students' learning activities and science learning outcomes. In the first cycle, the average learning outcome was 58.75 with a classical completeness of 43.75%, while in the second cycle it increased to an average of 82.50 with a classical completeness reaching 87.50%. This improvement shows that the Two Stay Two Stray learning model can create more active learning through cooperation between students, exchange of information between groups, and student involvement in the learning process, thus impacting on improving science learning outcomes.